The Implemention of Tanimbar Local Content Based on Descriptive Text to Improve Students’ Reading Comprehension at The Eight Grade of SMP Negeri 1 Wertamrian - Kristina Kelbulan; Pesparani D. Jabar; Marlina Kora (INDO PUBLISHING, 2026)
In this study, after conducting research, the researcher found the urgency of the problem, namely how the implementation of Tanimbar local content based on descriptive texts can improve reading comprehension among eighth-grade students at SMP Negeri 1 Wertamrian. The purpose of this study was to prove whetter the implemention of Tanimbar local content based on descriptive texts in eighth-grade classes at SMP Negeri 1 Wertamrian. To find the results in this study, the researcher used a class action research (CAR) method. Using a qualitative descriptive approach, the results of the study showed that of the 17 students who took the pre-test, 11 students had scores below the minimum passing grade, while 6 students had scores above the minimum passing grade. The results in cycle I showed that 6 students did not achieve a passing score, while 11 students did. Then, the results in cycle II showed that 17 students scored above the minimum passing grade, indicating that the success rate increased from the pre-test, post-test cycle I, and cycle II. Therefore, the researcher did not continue the research in the next cycle. Thus, the researcher can conclude from the results of this study that the results of this study entitled